Analysis of a kinematic self-centring seismic isolator. - Pinochet, Julio (Earthquake engineering & structural dynamics.)
This investigation deals with the analytical formulation and experimental validation of a prestressed reinforced concrete seismic isolator with kinematic constraints at both ends. The kinematic isolator was proposed initially as a low-cost solution for seismic protection of low-income people housing usually placed at the periphery of big cities where regular to bad soil conditions are common. So, the isolator is also a pile foundation with a central prestressed cable and two rolling steel surfaces at the top and bottom ends. By varying the shapes of the end rolling surfaces, different force?deformation constitutive relationships for the isolator may be obtained. Energy dissipation is introduced by yielding of passive reinforcement at the rolling interphase. Apart from stating the large-deformation formulation of the element, several relevant aspects of the behaviour of these devices are studied herein, such as the increase in the tension of the central prestressed cable, responsible for the self-centring action of the isolator, the floor uplift that results from the geometry of the isolator, and the vertical stability of the system. Experimental and theoretical results obtained for a group of 9 testing specimens show an excellent agreement in the force?deformation constitutive relationship. Although not the intent of this article, the device proposed may be extended directly as a coupling beam element for shear wall systems.